2013
DOI: 10.1096/fj.12-220533
|View full text |Cite
|
Sign up to set email alerts
|

Fusion‐activated cation entry (FACE)viaP2X4couples surfactant secretion and alveolar fluid transport

Abstract: Two fundamental mechanisms within alveoli are essential for lung function: regulated fluid transport and secretion of surfactant. Surfactant is secreted via exocytosis of lamellar bodies (LBs) in alveolar type II (ATII) cells. We recently reported that LB exocytosis results in fusion-activated cation entry (FACE) via P2X₄ receptors on LBs. We propose that FACE, in addition to facilitating surfactant secretion, modulates alveolar fluid transport. Correlative fluorescence and atomic force microscopy revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 56 publications
(90 reference statements)
4
43
0
Order By: Relevance
“…However, our data also demonstrates that selective pharmacological blocking of P2RX4 in WT mice results in diminished AAI as well, which provides convincing evidence for a functional relevance of P2RX4 signaling in asthma pathogenesis rather than a phenotype exclusively caused by the downregulated P2rx7 expression. Accordingly, a role of P2RX4 in airway remodeling by regulating ciliary beat, alveolar fluid transport and surfactant secretion of airway epithelial cells has been emphasized previously [35, 36]. Taken together, targeting P2RX4 might provide a potential promising therapy for allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 86%
“…However, our data also demonstrates that selective pharmacological blocking of P2RX4 in WT mice results in diminished AAI as well, which provides convincing evidence for a functional relevance of P2RX4 signaling in asthma pathogenesis rather than a phenotype exclusively caused by the downregulated P2rx7 expression. Accordingly, a role of P2RX4 in airway remodeling by regulating ciliary beat, alveolar fluid transport and surfactant secretion of airway epithelial cells has been emphasized previously [35, 36]. Taken together, targeting P2RX4 might provide a potential promising therapy for allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, P2XR4 activation was shown to increase both surfactant release and alveolar fluid reabsorption (24), which both have the potential to improve the course of inflammation. Briefly, extracellular adenosine triphosphate released from damaged cells acts as a triggering signal for the synthesis of IL-1", especially after macrophage priming by an inflammatory stimulus (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence also suggests a role for P2X 4 receptors therein. It has been demonstrated that activation of P2X 4 receptors following vesicle–plasma membrane fusion modulates the secretion and activation of pulmonary surfactant (Miklavc et al, 2011; Dietl et al, 2012; Thompson et al, 2013). …”
Section: Vesicular P2x4 Receptors Promote Surfactant Secretion Via Famentioning
confidence: 99%
“…Upon exocytosis of LBs, the P2X 4 receptor is readily part of the apical membrane as soon as membrane fusion is completed (Miklavc et al, 2009). Activation of P2X 4 in the presence of extracellular ATP then results in a transient, non-selective, inward-rectifying, cation current at the site of the fused vesicle (Miklavc et al, 2011; Thompson et al, 2013) ( Figure 1 ). The relatively high Ca 2+ permeability of P2X 4 receptors (North, 2002) causes a local, transient rise of [Ca 2+ ] c around the fused vesicle which promotes fusion pore expansion (Miklavc et al, 2011).…”
Section: Vesicular P2x4 Receptors Promote Surfactant Secretion Via Famentioning
confidence: 99%
See 1 more Smart Citation